Adaptive optics aberration correction for deep direct laser written waveguides in the heating regime - Bisch, N; Guan, J; Booth, M; Salter, P (Springer Berlin Heidelberg, 2019)
We demonstrate the negative effect of depth-dependent spherical aberration on femtosecond laser written waveguides fabricated in the high pulse repetition rate regime (1 MHz). Writing inside borosilicate Eagle 2000 glass, we show that, even in the cumulative heating regime, the focal distortion encountered at greater depths prevents the formation of single-mode waveguides. A liquid crystal spatial light modulator was incorporated for adaptive optics aberration correction, enabling low-loss single-mode waveguides to be written at various depths up to 1 mm. This result allows the accurate fabrication of 3D photonic devices consisting of uniform waveguides located at different depths.